PARE0009 COMMUNITY ADVISORY BOARD INPUT CAN MAKE LAY SUMMARIES OF CLINICAL TRIAL RESULTS MORE UNDERSTANDABLE. (2nd June 2020) - Welling, J.; Roennow, A.; Sauvé, M.; Brown, E.; Galetti, I.; Gonzalez, A.; Portales Guiraud, A. P.; Kennedy, A.; Leite, C.; Riggs, R. J.; Zheng, A.; Perkovic Popovic, M.; et al.
Abstract : Background: Under European Union (EU) Clinical Trial regulations, 1 clinical research sponsors (CRSs) must ensure all studies performed in the EU are accompanied by a trial summary for laypersons, published within 1 year of study completion. These lay summaries should disseminate clinical trial results in an easy-to-understand way for trial participants, patient and caregiver communities, and the general public. The European Patients Forum (EPF) 2 and European Patients' Academy on Therapeutic Innovation (EUPATI) 3 encourage CRSs to engage with patient organisations (POs) in the development of lay summaries. This recognises the patients' contribution to clinical research and supports the development of patient-focused material. Objectives: We share learnings from a collaboration between scleroderma POs and a CRS to create the SENSCIS® trial (NCT02597933 ) written and video lay summaries. Methods: A community advisory board (CAB), comprising representatives from 11 scleroderma POs covering a range of countries/regions, was formed based on the EURORDIS charter for collaboration in clinical research. 4 Through three structured meetings, over a seven-month period, the CAB provided advice on lay summary materials (written and video) drafted by the CRS' Lay Summary Group (Fig. 1 ). At each review cycle, the CAB advice was addressed to make content more understandable and more relevant for patients and the general public. Results: The CAB advised that the existence of lay summaries is not well known in the patient community and also recommended the development of trial-specific lay summary videos to further improve understandability of the clinical trial results for the general public. Videos are a key channel of communication, enabling access to information for people with specific health needs and lower literacy levels. Following CAB advice, the CRS developed a stand-alone video entitled "What are lay summaries?" and a trial-specific lay summary video. Revisions to lay summary content (written and video) included colour schemes, iconography and language changes to make content more understandable. For videos, adjustments to animation speed, script and voiceover were implemented to improve clarity and flow of information (Fig. 2 ). Approved final versions of lay summary materials are publicly available on the CRS website. Translation into languages representing trial-site countries is in progress to widen access to non-English speakers and, where possible, local versions are being reviewed by the patient community. Conclusion: Structured collection and implementation of CAB advice can make lay summary materials more understandable for the patient community and wider general public. References: [1]EU. Summaries of clinical trial results for laypersons. 2018 [2]EPF. EPF position: clinical trial results – communication of the lay summary. 2015 [3]EUPATI. Guidance for patient involvement in ethical review of clinical trials. 2018 [4]EURORDIS. Charter for Collaboration in Clinical Research in Rare Diseases. 2009 Disclosure of Interests: Joep Welling Speakers bureau: Four times as a patient advocate for employees of BII and BI MIDI with a fixed amount of € 150, 00 per occasion., Annelise Roennow: None declared, Maureen Sauvé Grant/research support from: Educational grants from Boehringer Ingelheim and Janssen., EDITH BROWN: None declared, Ilaria Galetti: None declared, Alex Gonzalez Consultant of: Payment made to the patient organisation (Scleroderma Research Foundation) for participation in advisory boards, Alexandra Paula Portales Guiraud: None declared, Ann Kennedy Grant/research support from: AS FESCA aisbl, Catarina Leite: None declared, Robert J. Riggs: None declared, Alison Zheng Grant/research support from: We get grants from Lorem Vascular; BI China, ; Jianke Pharmaceutical Co., Ltd.; Kangjing Biological Co., Ltd.; COFCO Coca-Cola to organize national scleroderma meetings, offer patients service, holding academic meetings and other public activities, there is also a small part of the grants used to pay the workers in our organization., Consultant of: I worked as a paid consultant for BI. Pay-per-job., Speakers bureau: I was invited once to be a speaker at BI China's internal meeting and they paid me., Matea Perkovic Popovic: None declared, Annie Gilbert Consultant of: I have worked as a paid consultant with BI International for over 3 years, since Sept 2016., Lizette Moros Employee of: Lizette Moros is an employee of Boehringer Ingelheim, Kamila Sroka-Saidi Employee of: Paid employee of Boehringer Ingelheim., Thomas Schindler Employee of: Employee of Boehringer Ingelheim Pharma, Henrik Finnern Employee of: Paid employee of Boehringer Ingelheim.